THE FACTOR OF SOCIAL MEMORY IN THE FORMATION OF NATIONAL SPIRIT AND PATRIOTISM (Conferencea, 2023)
The article examines the national and spiritual changes taking place in the world, the preservation of the national identity of peoples and the development of national social memory, ensuring the continuity of generations, young people’s comprehension of the past, the preservation of sociocultural heritage, leaving it for future generations, thereby strengthening historical thinking and social memory. It also reveals the fact that social memory is a socio-psychological phenomenon and the socio-political significance of the development of the national spirit and patriotism among young people.